Design and development of a real time thermal growth and temperature measurement system for the CNC vertical machining center - Rangarajan Sivakumar (2008)
“The first rule of any technology used in a business is that automation applied to an efficient operation will magnib the efficiency. The second is that automation applied to an inefficient operation will manify the inefficiency. (Bill Gates) ” In today’s heterogeneous environment product costs are aimed for bottom end and quality is aimed at top end. Manufacturing time of the product is getting shorter, so automating routine tasks is a key aspect.